The Impact of Tourism Policies on Local Economic Empowerment - Faozen; Siswanto, Edhi; Juhanda (Universitas Muhammadiyah Jember Press, 2025)
This study examines the impact of tourism policies on local economic empowerment in the Jember Regency through a literature study. The tourism policy implemented focuses on the development of community-based destinations with an inclusive, participatory, and sustainable approach. The results of the study show that the policy can improve community welfare through increasing employment, income, and cultural and environmental preservation. Success factors for economic empowerment include active community involvement, multi-stakeholder collaboration, capacity building through training, and the use of digital technology. However, challenges such as inequality of benefits, socio-cultural damage, and environmental risks must be a concern so that economic empowerment can run sustainably. The study recommends strengthening adaptive policies and further empirical research to support inclusive and sustainable tourism development